OUTCOMES OF ROTATIONAL ATHERECTOMY IN CALCIFIED PROXIMAL LEFT ANTERIOR DESCENDING (LAD) LESIONS IN THE CONTEXT OF TRIPLE VESSEL DISEASE - ASLAM, K; IQBAL, E; KHAN, FR; SAJJAD, W; KHAN, MS (Biological and Clinical Sciences Research Journal, 2023)
Percutaneous coronary intervention (PCI) has become more complex with the advancement of medical devices. One such device is the rotational atherectomy (RA), which uses a rotating diamond-coated burr to modify calcified lesions. This makes it easier to deliver balloons and stents to specific lesions. However, there is a lack of literature regarding the success of RA in calcified proximal 'left anterior descending (LAD) lesions' following PCI. To address this gap, a study was conducted to evaluate the clinical outcomes of RA in calcified proximal LAD lesions in triple vessel disease (TVD). The study included 112 patients who underwent PCI using RA between February 2022 and November 2022 at Lady Reading Hospital, Peshawar. Data was collected using a standard report structure, including operative and follow-up details and medical and demographic features. Retrospective data was collected using medical records and interviews with patients or doctors. The ethical committee approved the study. The participants had an average age of 68.4± 0.45 years, with 85 men (75.8%) and 40 (35.7%) with diabetes mellitus. The technical success rate was 97.6%, with 20 individuals (17.8%) experiencing significant adverse cerebral and cardiac events while hospitalized. At 1.5 years, 25 (22.3%) TVFs had occurred. Independent variables such as current smoking, chronic renal disease, history of cerebrovascular attack, left ventricle ejection fraction, and left central disease were assessed to predict TVF. Based on the results, the investigation showed that rotational atherectomy in calcified proximal LAD lesions had promising success rates.